2001
DOI: 10.1017/s0031182001008769
|View full text |Cite
|
Sign up to set email alerts
|

Expression and immunolocalization of the 14-3-3 protein of Schistosoma mansoni

Abstract: The 14-3-3 protein is a key player in signal transduction processes in various species. We have previously cloned and expressed the 14-3-3 of Schistosoma mansoni. Using the purified protein we have now raised antibodies against it. A highly specific, affinity-purified antibody preparation was employed for the localization of the 14-3-3 protein in the parasite, by both immunohistochemistry and immunoelectron microscopy. The results demonstrate wide distribution of this protein. It was observed in the female exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…The next most abundant ES protein was 14-3-3 protein, which was reported to localize to the excretory system and tegument of female S. mansoni worms (72) and has been used as a vaccine candidate against schistosomiasis (73). In S. japonicum ESP, several cytosolic glycolytic enzymes were unexpectedly identified, including enolase, pyruvate kinase, and GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…The next most abundant ES protein was 14-3-3 protein, which was reported to localize to the excretory system and tegument of female S. mansoni worms (72) and has been used as a vaccine candidate against schistosomiasis (73). In S. japonicum ESP, several cytosolic glycolytic enzymes were unexpectedly identified, including enolase, pyruvate kinase, and GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…In some parasites, such as Echinococcus multilocularis and Schistosoma mansoni, 14-3-3 proteins have been described to be immunogenic, and therefore have been promoted as potential vaccine targets (Schechtman et al 2001;Siles-Lucas et al 2008;Wang et al 2009). In addition, the 14-3-3 protein has been identified as a prominent product in the S. mansoni female worm reproductive system (Schechtman et al 2001). This may explain previous findings showing the female reproductive system as the main source of antigenic targets useful for the diagnosis of abdominal angiostrongyliasis caused by A. costarecensis (Bender, 2003).…”
mentioning
confidence: 99%
“…Mecozzi et al (2000) have demonstrated the localisation of calcineurin to the flame cells of the schistosomula and adult worms and Schechtman et al (2001) have found 14-3-3 protein in the protonephridial system of the female worm.…”
mentioning
confidence: 99%